Resting-state brain network analysis and applied evaluation of global developmental delay in preterm infants: A functional near-infrared spectroscopic study - Hengye Huang; Karol Kexin Sun; Dan Wu; Chuncao Zhang; Yanyan Huo; Yuan Tian; Guangjun Yu (Biosensors and Bioelectronics: X)
Global developmental delay (GDD) is a common neurodevelopmental disorder in children under 5 years of age. This study assessed the potential of functional Near-Infrared Spectroscopy (fNIRS) technology aiding diagnosis of GDD in premature infants and explored brain pathogenesis of GDD. This prospective cohort study was conducted between December 2020 and June 2023 among preterm infants in five hospitals in China. The primary outcome was the diagnosis of GDD. A 5-min fNIRS brain scan was performed in preterm infants at 4-, 8-, and 12-month corrected age in two hospitals. A diagnostic model based on fNIRS brain network and an integrated diagnostic model built on fNIRS data as well as birth head circumference was developed. Diagnostic models were assessed using the area under the curve (AUC) from receiver operating characteristic curves. Brain network analysis revealed significantly worse left-sided functional connectivity in GDD preterm infants. The fNIRS technique had satisfactory diagnostic value for GDD in all age groups. The diagnostic accuracy of the combined diagnostic model significantly improved. This study suggested that fNIRS could be considered for early screening and late auxiliary diagnosis of GDD in preterm infants. Furthermore, it can also be used to explore GDD brain pathogenesis.